Defenselessness and procedural overload in the New Procedural Labor Act - Gómez Guevara, Amalia Magdalena (2020)
This work tries to make an analysis regarding the problems detected in the application of the New Procedural Labor Act, as well as to contribute to one of the most important objectives of the labor procedural reform process, efficiency in the system. The fact of accepting that only exceptionally precisions or clarifications can be made regarding a claim, as long as it does not substantially alter it, has established a bad practice, because, under this argument, the litigants continue to modify their claim in labor matters; then, some courts reject it, in obviously inappropriate cases, while other courts accept it. Now, while it is true that there are still lawyers who do not adequately comply with a responsible and diligent practice at the time of filing the lawsuit, this can be solved with uniform criteria in each judicial district to avoid procedural overload and issue resolutions under the argument of application of the principles.